Sense of community and English perceived learning in a social networking site: a study of Facebook - Karimi, Leila; Tunku Ahmad, Tunku Badariah; Khodabandelou, Rouhollah (International Association of Computer Science and Information Technology Press (IACSIT Press), 2013)
The primary purpose of this study was to determine if a relationship exists between sense of community and English perceived learning in the social networking site-Facebook. 27 students from multiple nationalities who were members of English learning page participated in this study. The data were obtained via an online questionnaire with three scales. Results indicate that the students have positive feelings about Facebook as a tool for learning English, English perceived learning and sense of community. Low correlation exists between sense of community and English perceived learning.